Differences in Clinical and Echocardiographic Parameters between Paroxysmal and Persistent Atrial Flutter in the AURUM 8 Study: Targets for Prevention of Persistent Arrhythmia?. Issue 2 (4th February 2013) - LICKFETT, LARS; MITTMANN‐BRAUN, ERICA; WEISS, CHRISTIAN; SPENCKER, SEBASTIAN; JUNG, WERNER; HAVERKAMP, WILHELM; WILLEMS, STEPHAN; DENEKE, THOMAS; KAUTZNER, JOSEF; WIEDEMANN, MICHAEL; SIEBELS, JÜRGEN; PITSCHNER, HEINZ F.; et al.
<x xml:space="preserve">Abstract</x> Purpose Cavotricuspid isthmus‐dependent atrial flutter (AFL) can occur in a paroxysmal or persistent pattern. The aim of this study was to identify clinical, echocardiographic, and electrophysiological risk factors independently associated with persistence of AFL. Methods Patients of the recently published AURUM 8 study with paroxysmal versus persistent AFL were compared with respect to clinical and echocardiographic baseline characteristics as well as procedural parameters. The AURUM 8 study is a randomized, multicenter clinical trial comparing the efficacy and safety of gold versus platinum‐iridium 8‐mm‐tip ablation. AFL was paroxysmal in 218 patients and persistent in 210 patients. Results Univariate analysis revealed that patients with persistent AFL had higher New York Heart Association class (P = 0.002), shorter time since 1st AFL episode (median 0.18 vs 0.34, P = 0.037), a higher prevalence of previous coronary artery bypass grafting surgery (17% vs 9%, P = 0.02), left ventricular hypertrophy (17% vs 8%, P = 0.005), dyspnea during AFL (P < 0.001), mitral regurgitation (P = 0.002), tricuspid regurgitation (P = 0.049), and pulmonary hypertension (P = 0.01). Palpitations during AFL were less frequent in patients with persistent AFL (P = 0.001). Multivariate analysis revealed that age, weight, AFL diagnosis after initiation of class IC or III antiarrhythmic drugs for atrial fibrillation, history of left ventricular hypertrophy, dyspnea during AFL and mitral regurgitation on echocardiography were significant independent variables associated with persistent AFL. A history of atrial fibrillation and palpitations during AFL were independently associated with paroxysmal AFL. Conclusions We were able to identify clinical and echocardiographic risk factors associated with persistence of typical AFL. Treatment of these risk factors can potentially not only prevent the transition from paroxysmal to persistent AFL, but maybe also the development or initiation of AFL in general.